Foreign consultants and counterparts : problems in technology transfer - Scott-Stevens, Susan (Routledge, 2018)
Even though concern about and interest in technology transfer have existed since the 1950s, it has become of increasing importance to lesser-developed and developing countries since the 1970s. The transfer of technology in general, and in particular the transfer of technical knowledge, lies at the heart of the North-South debate. There is an abundance of literature on technology transfer in almost every field of interest--policy, practice, applied case studies, and general recommendations--but little, if any, of the information is integrated. It remains widely distributed throughout the fields of economics, business, rural sociology, and anthropology. The same may be said for various studies of consultants as change agents. On the other hand, studies of counterparts--host country professionals--have been almost entirely neglected, with the exception of their implied roles as innovators or acceptors. There have been few attempts to tie practice to theory, theory to research, or research to practice. This volume attempts to provide the link between theory, research, and practice. Based upon research conducted at two large-scale water resource development projects in Indonesia, it focuses upon the problems and solutions encountered by two primary sets of people involved in the transfer of technical knowledge--foreign consultants and host country counterparts. Dr. Scott-Stevens presents a unified and applied approach to many of the cross-cultural theories, issues, and problems common to the transfer of technical knowledge across cultures.